The attributes of e-commerce on e-customer satisfaction - Zi, Meng Wang; Toh, Pei Sung; Brahim Chekima (Macrothink Institute, 2022)
Due to the advancement of Internet technology and the globalization of commerce, e-commerce is developing at an unexpected speed. With the rise of China’s e-commerce industry and the substantial increase in the number of merchants, the competition in its industry has also increased. In this context, consumer satisfaction is all affected, so this paper conceptually discusses the attributes of e-commerce on e-customer satisfaction. The reviewed literature highlights factors and issues of importance in developing a research framework for future empirical research on this topic.